Health related quality of life in adult primary Ciliary dyskinesia patients in Cyprus: development and validation of the Greek version of the QOL-PCD questionnaire - Ioannou, Phivos; Kouis, Panayiotis; Kakkoura, Maria G.; Kaliva, Margarita; Toliopoulou, Aristoula; Andreou, Kyriacos; Behan, Laura; Lucas, Jane S.; Papanikolaou, Vicky; Charalambous, George; Middleton, Nicos; Yiallouros, Panayiotis K. (My University, 2020)
Background: The QOL-PCD questionnaire is a recently developed Health Related Quality of Life (HRQoL) instrument for Primary Ciliary Dyskinesia. The aim of this study was to translate the adult QOL-PCD questionnaire into Greek language and to conduct psychometric validation to assess its performance. Methods: Forward translations to Greek and backward translation to English were performed, followed by cognitive interviews in 12 adult PCD patients. The finalized translated version was administered to a consecutive sample of 31 adult, Greek speaking PCD patients in Cyprus for psychometric validation, which included assessment of internal consistency, test-retest reliability, construct and convergent validity. Internal consistency was assessed by Cronbach's alpha test in terms of the overall and sub-scales. Test-retest reliability was assessed by repeat administration of the questionnaire within 2 weeks and calculation of the intra-class correlation (ICC). Construct validity was assessed by comparing different groups of patients based on a-priori hypotheses and convergent validity was evaluated by examining associations between the QOL-PCD and SF-36 questionnaires. Results: Moderate to good internal consistency was observed (Cronbach's α: 0.46-0.88 across sub-scales) and test-retest reliability assessment demonstrated good repeatability for most scales (ICC: 0.67-0.91 across subscales). Patients of female gender, older age and lower lung function exhibited lower QOL-PCD scores in general, while high correlations for most QOL-PCD scales with corresponding SF-36 scales were observed, in particular for physical functioning (r = 0.78, p < 0.05). Conclusion: The adult version of QoL-PCD questionnaire has been translated according to international guidelines resulting to a cross-culturally validated Greek version which exhibited moderate to good metric properties in terms of internal consistency, stability, known-group and convergent validity.
Keywords: Primary Ciliary dyskinesia; Psychometric testing; Quality of life